Valerius Maximus and a memory to the measure of Tiberius - Schniebs, Alicia (Romanitas - Revista de Estudos Grecolatinos, 2014)
In this article we will analyze Valerio Maximus’s construction of two institutions, the disciplina militaris and censura, which is known as guardians of peace and stability. We will show that this construction is part of the transformations caused by the installation of the autocratic regime that affects the role of the elite and that, after the succession instrumented by Augustus, seems to be an irreversible situation.
Keywords: Principatus; Disciplina Militaris; Censura; Valerius Maximus; Tiberius